91.5k views
5 votes
Need help with this question!!!
Pls explain!!!

3=-(4x+7)+3x

User Xilmiki
by
6.0k points

1 Answer

3 votes

Answer:

x=-10

Explanation:

3=-(4x+7)+3x

move all terms to the left:

3-(-(4x+7)+3x)=0

calculate terms in parentheses: -(-(4x+7)+3x), so:

-(4x+7)+3x

add all the numbers together, and all the variables

3x-(4x+7)

get rid of parentheses

3x-4x-7

add all the numbers together, and all the variables

-1x-7

Back to the equation:

-(-1x-7)

get rid of parentheses

1x+7+3=0

add all the numbers together, and all the variables

x+10=0

move all terms containing x to the left, all other terms to the right

x=-10

User Mr Zorn
by
5.3k points